The effect of single-leg hurdle hop plyometric training on the improvement of lower limb explosive power in badminton athletes aged 12–15 years - Oktaviano, Achmed Isyam; Firmansyah, Awang; Wismanadi, Himawan; Rusdiawan, Afif (Universitas Sriwijaya, 2026)
Research Problems: Lower limb explosive power is a fundamental physical component in badminton, as it supports rapid directional changes, lunges, and jump smashes during match play. In adolescent athletes aged 12–15 years, structured and sport-specific training is essential to optimise long-term athletic development. Plyometric training, particularly unilateral exercises such as the single-leg hurdle hop, is considered effective in enhancing neuromuscular performance and explosive strength. Research Objectives: This study aimed to examine the effect of single-leg hurdle hop plyometric training on lower limb explosive power in youth badminton athletes. Methods: A pre-experimental study with a one-group pretest–posttest design was employed. The participants were 25 badminton players (male and female) aged 12–15 years (mean height = 155 cm; mean body mass = 45.76 kg; mean BMI = 19.02). Lower limb explosive power was measured using the vertical jump test. Data were analyzed using normality testing and a paired-samples t-test to examine pre- and post-intervention differences. Results: The results revealed a statistically significant improvement in lower limb explosive power following the training intervention (p = 0.01, p < 0.05). Conclusion: These findings indicate that single-leg hurdle hop plyometric training is effective in enhancing explosive power in adolescent badminton athletes. Future research is recommended to incorporate control groups, longer intervention periods, and motivational strategies to optimise training adherence and performance outcomes.